Can Transcutaneous CO2 Tension Be Used to Calculate Ventilatory Dead Space? A Pilot Study - Pradeep H. Lakshminarayana; Adiba A. Geeti; Umer M. Darr; David A. Kaufman (Critical Care Research and Practice)
Dead space fraction (Vd/Vt) measurement performed using volumetric capnography requires arterial blood gas (ABG) sampling to estimate the partial pressure of carbon dioxide (PaCO2). In recent years, transcutaneous capnography (PtcCO2) has emerged as a noninvasive method of estimating PaCO2. We hypothesized that PtcCO2 can be used as a substitute for PaCO2 in the calculation of Vd/Vt. In this prospective pilot comparison study, 30 consecutive postcardiac surgery mechanically ventilated patients had Vd/Vt calculated separately using volumetric capnography by substituting PtcCO2 for PaCO2. The mean Vd/Vt calculated using PaCO2 and PtcCO2 was 0.48 ± 0.09 and 0.53 ± 0.08, respectively, with a strong positive correlation between the two methods of calculation (Pearson’s correlation = 0.87, p<0.05). Bland-Altman analysis showed a mean difference of −0.05 (95% CI: −0.01 to −0.09) between the two methods. PtcCO2 measurements can provide a noninvasive means to measure Vd/Vt, thus accessing important physiologic information and prognostic assessment in patients receiving mechanical ventilation.